Respectful maternity care among women who gave birth at public hospitals in Hadiya Zone, Southern Ethiopia - Tilahun Mengistie; Teshale Mulatu; Afework Alemayehu; Tesfaye Assebe Yadeta; Merga Dheresa (Frontiers Media S.A., 2022)
BackgroundA compassionate and respectful care during pregnancy and childbirth is one of the essential components of safe motherhood. However, most of the women in developing countries experience disrespectful and abusive maternity care during childbirth. Hence, this study assessed the status of respectful maternity care and associated factors to bridge the gap.MethodologyFacility-based cross-sectional study was conducted among mothers who delivered in public Hospitals in the Hadiya Zone, South Ethiopia from March 01 to 30, 2020. Data were collected using a pretested questionnaire through face-to-face interviews. Descriptive statistics was computed and multivariable logistic regression was fitted to identify predictors. Adjusted Odds Ratio (AOR) with 95% Confidence Interval was used to show the strength of association and level of significance was declared at P-value < 0.05.ResultThis study showed that 67.8 % (95% CI: 62.4-70.8%) of mothers received respectful maternal care. Being married [AOR: 2.17, 95% CI (1.03-6.93)], Cesarean section delivery [AOR: 2.48, 95% CI (1.03-5.97)], and absence of complications during child birth [AOR: 4.37, 95% CI (1.41-13.56)], were significantly associated with respectful maternity care.ConclusionsThe level of RMC in this study was moderate. Being married, Cesarean section delivery, and absence of complications during child birth were identified predictors of respectful maternity care. Therefore, tailored interventions aimed at improving respectful maternity care should target unmarried women, and women with complications of labor regardless of mode of delivery.